Arbitrage power and the disappearing financialized firm - Ronen Palan; Richard Phillips (Finance and Society, 2022)
Modern corporations have increasingly been adopting a decentred, layered, and multi-jurisdictional form as a strategy of boundary manipulation known amongst tax lawyers and accountants as "regulatory arbitrage". The argument we put forward in this article is that the scholarly work that treats these strategies as mere tax avoidance practices has contributed to an underestimation and misrecognition of the way contemporary multinationals operate in markets. These strategies, which we explain in terms of arbitrage power, exploit the difference between exchanges in an imaginary 'smooth' market of the economic textbook and a global market that is divided among legal authorities, each imposing their own rules, regulations, and taxations. Arbitrage power exploits differences between the location of market exchange and the location of the registration of property title transfers, combining this with a manipulation of formal systems for recognizing business enterprises in order to escape some or all the rules and regulations of society. The result is a marked difference between the 'brochure multinational', the way multinationals are seen and presented in their glossy brochures, and the way multinationals are legally and practically organized nowadays.
Keywords: 300; Multinational enterprises; power; jurisdictional arbitrage; evolutionary economics; globalization